Which expression represents the distance between the points (a, 0) and (0, 5) on a coordinate grid? StartRoot a squared + 5 EndRoot StartRoot a squared + 25 EndRoot StartRoot (a minus 25) squared EndRoot StartRoot (a minus 5) squared EndRoot
Answer:Which expression represents the distance between the points (a, 0) and (0, 5) on a coordinate grid? StartRoot a squared + 5 EndRoot StartRoot a squared + 25 EndRoot StartRoot (a minus 25) squared EndRoot StartRoot (a minus 5) squared EndRoot
Step-by-step explanation:
0, 5) on a coordinate grid? StartRoot a squared + 5 EndRoot StartRoot a squared + 25 EndRoot StartRoot (a minus 25) squared EndRoot StartRoot (a minus 5) squared EndRoot
The distance between the two points is given by:
[tex]d = \sqrt{a^2 + 25}[/tex]
Which expression represents the distance between the points?
The distance between two points (x₁, y₁) and (x₂, y₂) is given by:
[tex]d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2}[/tex]
Then for the given points, that are (a, 0) and (0, 5) the distance is given by:
[tex]d = \sqrt{(0 - a)^2 + (5 - 0)^2} \\\\d = \sqrt{a^2 + 25}[/tex]
Then the correct option is the second one, the square root of the sum between a squared and 25.
If you want to learn about distance between points:
https://brainly.com/question/7243416
#SPJ2
The diameter of a circle is 58 feet. What is the circle's circumference?
Use 3.14 for .
Answer:
182.12
Step-by-step explanation:
2πr , then substitute the numbers
Answer:
182.12ft
Step-by-step explanation:
Just remember to divide the diameter by two to get the radius.
58/2 = 29
C=2 π r
C = 2 * 3.14 * 29= 182.12ft
PLS HELP!!!!Pre-Cal
1. Find the equation of a parabola with vertex (2, -1), opens upward and has focal width of 16.
2. Find the equation of a parabola with focus (2, -3) and directrix x = 5.
The equation of the first parabola with vertex (2, -1), opens upward with a focal width of 16 is (x-2)² = 16*(y+1). The equation of the second parabola with a focus (2, -3) and directrix x = 5 is (x-2)² = -24*(y-5).
Explanation:1. For a parabola that opens upward with vertex (h, k) and focal width 4p, the equation is given by: (x-h)² = 4p*(y-k). Given the vertex (2, -1) and focal width of 16, we can deduce that 4p = 16, so p = 4. Plug these values into the formula to get the equation of the parabola: (x-2)² = 16*(y+1).
2. For a parabola with a focus (h, p) and directrix x=d, the equation is (x-h)² = 4p*(y-d). Given the focus (2, -3) and directrix x = 5, meaning h = 2, p = -3, and d = 5. This gives us the equation of the parabola: (x-2)² = -24*(y-5).
Learn more about Equation of a Parabola here:https://brainly.com/question/35546720
#SPJ6
The equation of the first parabola described is (y+1) = (x-2)^2. The equation of the second parabola, given the focus at (2,-3) and the directrix at x = 5, is (x-2) = -(1/12)(y+3)^2.
Explanation:1. The standard form of a parabola that opens upward or downward is (y-k)=(1/4p)(x-h)^2, where (h,k) is the vertex and p is the distance from the vertex to the focus. In this case, h is 2, k is -1 and the focal width is 4p which is given as 16. So p = 16/4 = 4. So, the equation of the parabola is (y+1) = (x-2)^2.
2. The standard form of a parabola that opens to the right or to the left is (x-h)= (1/4p)(y-k)^2. In this case, the focus is (2,-3) and the directrix is x=5. From these, we know h=2, and since the directrix is to the right of the focus, p=h-5 is negative, so p=2-5=-3. The vertex of the parabola is thus (2,-3). So, the equation of the parabola is "(x-2) = -(1/12)(y+3)^2".
Learn more about Parabola equations here:https://brainly.com/question/11911877
#SPJ6
30% of $40 is how much money
Answer:
$12
Step-by-step explanation:
30% is 0.3
So 0.3 × 40 = 12
What happens when demand exceeds supply?
A.
prices decrease
B.
prices increase
C.
prices remain stable
Answer:
B. Prices increase.
Step-by-step explanation:
When demand for a product is greater than the product's supply, that increases the value of said product, and thus they bring the price up.
When demand exceeds supply, it's referred to as a shortage or excess demand, and generally leads to an increase in prices. Sellers are able to charge more because more consumers are vying for a limited number of goods.
Explanation:When demand exceeds supply in economic terms, it leads to a situation called excess demand or shortage. In this scenario, more people want a product than the amount of the product available. As a result of this excess demand, prices generally increase. This increase happens due to the basic law of demand and supply. Since more consumers are chasing a limited number of goods, sellers can charge higher prices. This increase in prices can help reduce the demand and bring the market back into equilibrium.
For instance, consider a situation where new smartphones are released, and the demand outstrips the supply. The prices will likely increase because people are willing to pay a higher price to secure one of the limited handsets.
Learn more about demand exceeds supply here:https://brainly.com/question/2543482
#SPJ6
What is the answer to this?
Answer:
B.
Step-by-step explanation:
Answer:
B is the correct answer
Step-by-step explanation:
Rewrite the following the form log (c) log (20) - log (5)
Final answer:
The expression log(c) log(20) - log(5) is simplified using the quotient rule for logarithms to log(c) log(4), by subtracting the logs and simplifying the inside expression from 20/5 to 4.
Explanation:
The student's question involves simplifying a logarithmic expression. The initial expression is log(c) log(20) - log(5). To simplify this expression, we can use logarithmic properties, specifically the quotient rule of logarithms, which states that log(a/b) = log(a) - log(b).
Applying this property to the given expression, we combine the two logs that are subtracted:
log(20) - log(5) = log(20/5). Simplifying the division inside the log gives us:
log(4). Therefore, the simplified expression is log(c) log(4).
0
2
2
6
6
7
8
9
10
TIME REN
36:
A baseball player had 4 hits in 8 games. At this rate, how many hits will the baseball player have in the next 28 games?
Answer:
14 hits in 28 games
Step-by-step explanation:
every 2 games there is 1 hit
i need help please
Answer:2nd one
Step-by-step explanation:
Answer:
1/2 and 1/3
Step-by-step explanation:
1/2 can have a denominator of 6 by multiplying by 3
[tex]\frac{1}{2} *\frac{3}{3} =\frac{3}{6}[/tex]
1/3 can have a denominator of 6 by multiplying by 2
[tex]\frac{1}{3} *\frac{2}{2} =\frac{2}{6}[/tex]
Plz answer! Will mark brainliest if correct!
Answer:
order: 37, 40, 42, 47, 52, 54, 57, 60
a) mean: 48.625
b) difference: 340.375
c) 47.5 difference (between mean and mad)
d) 7.125
5.4 is an integer.
True
OR
False
Answer:
False
Step-by-step explanation:
As integer is a whole number that is not a fractional number that can be positive, negative, or zero.
Answer:
false
Step-by-step explanation:
An integer is a whole number. integers can't have a decimal places.
Every month, $25 is withdrawn from Calvin’s account to pay for his gym membership. He has enough savings to withdraw no more than $225. For how many months can Calvin pay for his membership?
Answer:
9 months.
Step-by-step explanation:
225 / 25 = 9
Feel free to let me know if you need more help! :)
Answer:
9
Step-by-step explanation:
225/25 is 9
Ms Davis says that you can use the area of a a circle to figure out its circumference,but a student disagreed.Who is correct?Use Area= 78.5m to solve the problem and then explain with a paragraph who is correct?
Answer:
The student is correct.
Step-by-step explanation:The circle's circumference is the distance around the circle. To find out the circle's circumference, you will NEED the radius. Without the radius OR diameter, there will be no way of telling what the circumference is with just the area.
Tomos is a skier he completed a ski race in 2 min 6 seconds the race was 525 m in length. tomos assumes that his average speed is the same for each race. using this assumption, work out how long tomos should take to complete an 800 m race give your answer in minutes and seconds
Answer:
3 min 12 seconds
Step-by-step explanation:
Using the conversion
1 minute = 60 seconds, then
2 min 6 seconds = (2 × 60) + 6 = 120 + 6 = 126 seconds
Divide 126 by 525 then multiply by 800, that is
time = [tex]\frac{126}{525}[/tex] × 800 = 192 seconds = 3 min 12 seconds
Final answer:
After calculating Tomos's average speed from the 525 m ski race, we use that speed to determine that it should take him approximately 3 minutes and 12 seconds to complete an 800 m race.
Explanation:
To determine how long Tomos should take to complete an 800 m race given his average speed, we start by calculating his speed during the 525 m race. Tomos completed the 525 m ski race in 2 minutes and 6 seconds, which is a total of 126 seconds.
Firstly, we calculate Tomos's average speed:
Average speed (v) = Total distance (d) / Total time (t)
v = 525 m / 126 s
v = 4.1667 m/s (approximately)
Now, to find out how long it will take Tomos to ski 800 m at the same speed, we use the formula:
Time (t) = Distance (d) / Speed (v)
t = 800 m / 4.1667 m/s
t = 192 seconds (approximately)
Finally, we convert the time from seconds to minutes and seconds:
There are 60 seconds in a minute, so:
Time = 192 s = 3 minutes and 12 seconds
Therefore, it should take Tomos approximately 3 minutes and 12 seconds to complete an 800 m race at his average speed.
H(r) = (r+1)(r+8) what are the zeros of the function
Answer:
all work is pictured and shown
11. How is the graph of g(x) = 5x² - 2
related to the graph of f(x)= x2?
The graph of both functions are positive, thus the graph is increasing in the upward direction.
The graph of a quadratic equation.
The graph of a quadratic equation is a parabolic curve or a U-shaped curve. From the given function, the parent function is f(x) = x² and the g(x) is the transformed function of the original function.
The function of g(x) = 5x² - 2 is vertically stretch by 5 units and it is shifted vertically downward by 2 units.
Thus, we can say that the graph of g(x) = 5x² - 2 is related to f(x) = x² because of the vertical stretch and the vertical shift. Also, since both functions are positive, the graph is increasing in the upward direction.
Suppose the depth of a lake can be described by the function y = 323(0.976)x, where x represents the number of weeks from today. Today, the depth of the lake is 323 ft. What will the depth be in 6 weeks? Round your answer to the nearest whole number. The depth of the lake will be ft. in 6 weeks
Answer:
The dept of the lake will be 279 ft in 6 weeks
Step-by-step explanation:
We are given that the depth of a lake can be modeled by the function
[tex]y = 323(0.976)^{x}[/tex]
Where x is the number of weeks and y is the depth of lake in feet
The depth of the lake today is (x=0)
[tex]y = 323(0.976)^{0}[/tex]
[tex]y=323[/tex] [tex]ft[/tex]
The depth of the lake after 6 weeks will be (x=6)
[tex]y = 323(0.976)^{6}[/tex]
[tex]y = 323(0.864)[/tex]
[tex]y=279[/tex] [tex]ft[/tex]
Therefore, the dept of the lake will be 279 ft in 6 weeks.
Can you help me please??
The probability that a child will learn to swim before age 6 is 0.312. If you take a group of 12 children, what is the probability that 1 or fewer of the children will learn to swim before age 6? (Round your answer to 3 decimal places if necessary.)
Answer:
The probability of 1 or less children from that group to learn how to swim before 6 years of age is 0.072
Step-by-step explanation:
In this case we need to compute the probability of none of these 12 children learns to swim before 6 years of age. This is given by:
p(0) = (1 - 0.312)^(12) = 0.688^(12) = 0.01124
We now need to calculate the probability that one child learns to swim before 6 years of age.
p(1) = 12*0.312*(1 - 0.312)^(11) = 3.744*(0.688)^(11)
p(1) = 3.744*0.01634
p(1) = 0.0612
The probability of 1 or less children from that group to learn how to swim before 6 years of age is:
p = p(0) + p(1) = 0.01124 + 0.0612 = 0.07244
The probability that 1 or fewer of the 12 children will learn to swim before age 6 is approximately 0.072 when rounded to three decimal places.
1. Given:
- Probability that a child will learn to swim before age 6, ( p = 0.312 )
- Number of children, ( n = 12 )
2. Calculating ( P(X = 0) ):
[tex]\[P(X = 0) = \binom{12}{0} (0.312)^0 (1 - 0.312)^{12}\]\[P(X = 0) = 1 \times 1 \times (0.688)^{12}\]\[P(X = 0) \approx (0.688)^{12}\][/tex]
Using a calculator for [tex]\((0.688)^{12}\)[/tex]:
[tex]\[(0.688)^{12} \approx 0.0088\][/tex]
3. Calculating ( P(X = 1) ):
[tex]\[P(X = 1) = \binom{12}{1} (0.312)^1 (1 - 0.312)^{11}\]\[P(X = 1) = 12 \times 0.312 \times (0.688)^{11}\][/tex]
Using the binomial cumulative distribution function (CDF):
[tex]\[P(X \leq 1) = \sum_{k=0}^{1} \binom{12}{k} (0.312)^k (0.688)^{12-k}\][/tex]
Using the binomial probability tables or calculator, we get:
[tex]\[P(X = 0) \approx 0.0088\]\[P(X = 1) \approx 0.0623\][/tex]
Summing these:
[tex]\[P(X \leq 1) \approx 0.0088 + 0.0623 = 0.0711\][/tex]
Thus, the probability that 1 or fewer of the 12 children will learn to swim before age 6 is approximately 0.0711, which rounds to 0.072.
Find the rule of f(2)
Answer:
f(2) = - 16
Step-by-step explanation:
Given
f(x) = - [tex](4)^{x}[/tex]
To evaluate f(2) substitute x = 2 into f(x)
f(2) = - [tex](4)^{2}[/tex] = - 16
Explain how you determine each of the two expressions of the equation when the mathematical statement is given in words.
Answer:
The two expressions of an equation are separated by an equal sign. When the statement is given in words, the equal sign is indicated by the word “is” or the words “the same as.”
Step-by-step explanation:
Two expressions of the equation by properly interpreting the words into appropriate signs and digits.
what is two expressions of the equation?An equation is a mathematical statement that two expressions are equal. The solution of an equation is the value that when substituted for the variable makes the equation a true statement. To achieve our goal, we use two principles of equality, the addition principle and the multiplication principle.
What is an expression with 2 terms?A binomial expression is an algebraic expression which is having two terms, which are unlike. Examples of binomial include 5xy + 8, xyz + x3, etc.
What is an expression in algebra example?Algebraic expressions include at least one variable and at least one operation (addition, subtraction, multiplication, division). For example, 2(x + 8y) is an algebraic expression.
Learn more about two expression of the equation, refer
https://brainly.com/question/21628639
#SPJ2
Jake earns $7.50 per hour working at a local car wash. The function,
ƒ
ƒ
(
x
)
=
7.50
x
, relates the amount Jake earns to the number of hours he works. Write the inverse of this relation
Answer:
f(x) = y
y = 7.50x
To find the inverse, swap x and y
x = 7.50y
Now solve for y
y = x/7.50
f-1(x) = x/7.50
Graph a line that contains the point (-5,-3) and has a slope of -2
Answer:
-->
Step-by-step explanation:
Graph (-5,-3) and use the slope, -2, to find another point. -2 can also be written as [tex]-\frac{2}{1}[/tex]
[tex]\frac{rise}{run} =\frac{-2}{1}[/tex] and [tex]\frac{rise}{run} =\frac{2}{-1}[/tex] **
Use both. This works because either way, they will lie on the same line with the same slope. So, starting at (-5,-3), go down two points (-)* and to the left 1 (+)*, then, starting at (-5,-3) again, go up two points (+)* then to the right 1 point (-)*.
* If the number is negative, you either go down or to the right. If the number is positive, you go up and to the left.
**Rise over run refers to the change in the y-axis and the change in the x-axis: [tex]\frac{rise}{run} =\frac{y-axis}{x-axis}[/tex]. Only one number is negative because, if both were negative, that would make a positive number, but the slope is -2, not 2.
Another way you could do this is by finding points first. All you need to do is turn the slope into a "point". Remember, 2 is the y and 1 is the x:
[tex]-2=-\frac{2}{1} = (1,-2)[/tex] and [tex](-1,2)[/tex]
Then, using (-5,-3) and your new points, add them separately:
[tex](-5,-3)+(1,-2)\\(-5+1,-3+(-2))\\(-5+1,-3-2)\\(-4,-5)[/tex]
(-4,-5) is one point
[tex](-5,-3)+(-1,2)\\(-5+(-1),-3+2)\\(-5-1,-3+2)\\(-6,-1)[/tex]
(-6,-1) is another point. Connect the three points. You can check your work on the graph:
Is there a vertical shift? What is it?
2(x+2) – 5
I NEED HELP ASAP!!
Answer:
Yes, there s a vertical shift to the right by 1
Step-by-step explanation:
If you distribute the 2 among the (x+2) you get:
2x+4-5
Combine like terms:
2x+1
There fore the line shifts right by one.
Answer:
Yes, the equation shifts down by five.
Step-by-step explanation:
In equations, vertical shifts happen when the ENTIRE equation, or y, is added or subtracted a number.
Horizontal shifts happen when JUST the x value is added or subtracted a number, but this is a little different.
The formula for the equation you gave us is
m(x - h) + k
Since "h" is already negative, we have to flip the sign of the +2, so the horizontal shift would be LEFT two units.
As far as the vertical shift goes, we just have to look at the "+k."
Since k = -5, the equation shifts down five units.
a school admissions office accepts 3 out of every 5 applicants. given that the school accepted 750 students how many students applied?
Answer:
1250 Students applied.
Step-by-step explanation:
If you set it up as a proportion and then cross multiply, it comes out to 3x=3750 so then you would simplify and get x = 1250 as your answer!
Hope this helps!
What is the missing constant term in the perfect square that starts with x^2+2x
To find the missing constant term, we want to think about what two numbers would add up to 2. Of the numbers we've thought of, we want to find the numbers that are the same. In this case, that would be 1 and 1. If we multiply, or square, 1 and 1 together, we get 1. So, the missing constant term in the perfect square given here would be 1.
Hope this helps!! :)
How do i solve this? - Linear Functions
Answer:
solve for y
Step-by-step explanation:
[tex]5x-2y=-10[/tex]
subtract 5x from both sides
[tex]5x-5x-2y=-10-5x[/tex]
[tex]-2y=-10-5x[/tex]
Divide each term in the equation by -2
[tex]\frac{-2y}{-2}=\frac{-10}{-2} -\frac{-5x}{-2}\\\\y=\frac{-10}{-2} +\frac{-5x}{-2} \\\\y=5+\frac{5x}{2}[/tex]
(negative+negative=positive)
re-write in slope-intercept form [tex]y=mx+b[/tex] , where m is the slope and b is the y-intercept
[tex]y=\frac{5}{2}x+5[/tex]
Now you know that the slope is [tex]\frac{5}{2}x[/tex] and the y-intercept is [tex]5[/tex].
Now, to graph, you just need to choose random values for x (like 0,1,2,3 or any other number) and insert into the equation [tex]y=\frac{5}{2}x+5[/tex] to find the points, or you can just use the slope. To find the x-intercept, do the following:
make y equal to 0
[tex]0=\frac{5}{2}x+5[/tex]
Solve for x:
simplify [tex]\frac{5}{2}x[/tex]
[tex]0=\frac{5x}{2} +5[/tex]
Subtract 5 from both sides
[tex]0-5=\frac{5x}{2}+5-5\\ \\-5=\frac{5x}{2}[/tex]
Multiply both sides by 2
[tex]2(-5)=2(\frac{5x}{2})\\\\-10=5x[/tex]
Divide both sides by 5
[tex]\frac{-10}{5}= \frac{5x}{5}\\\\-2=x[/tex]
Flip
[tex]x=-2[/tex]
The x-intercept is -2.
The system of equations has no solution:
y=2/3x-5
4x - 6y = 30
true or false?
1. y = 2/3x - 5
2. 4x - 6y = 30
Divide 2. by 2
3. 2x - 3y = 15
Substitute 1. into 3.
4. 2x - 3(2/3x - 5) = 15
5. 2x - 2x + 15 = 15
6. 15 = 15
False. There are an infinite number of solutions.
What is 60 over 40 in a mixed fraction
Answer:
1 1/2
Step-by-step explanation:
60/40 = (60 ÷ 20)/(40 ÷ 20) = 3/2; 3 > 2 => improper fraction Rewrite: 3 ÷ 2 = 1 and remainder = 1 => 3/2 = (1 × 2 + 1)/2 = 1 + 1/2 = = 1 1/2, mixed number (mixed fraction)
Hope this helped!
Answer:
1 1/2
Step-by-step explanation:
40 can go into 60 1 time
simplify the rest
Is the following shape a right triangle? How do you know?
O
O
A. There is not enough information to determine.
B. No, there is no right angle.
O
c. No, the side lengths do not fit the Pythagorean theorem.
O
D. Yes, two sides are perpendicular, and the side lengths fit the
Pythagorean theorem.
PREVIOUS
a
e
9
Answer:
D. Yes, two sides are perpendicular, and the side lengths fit the
Pythagorean theorem.
Option B is correct as the shape lacks a right angle and its side lengths do not conform to the Pythagorean theorem, despite having two perpendicular sides.
What is a right-angled triangle?A right-angled triangle is a geometric shape that has one internal angle measuring exactly 90 degrees. This angle, known as the right angle, is formed by the intersection of two sides of the triangle.
The other two angles in the triangle are acute angles, which means they measure less than 90 degrees. The side opposite the right angle is called the hypotenuse, and it is the longest side in the triangle.
The other two sides are called the legs, and they form the right angle. The lengths of the legs and the hypotenuse of a right-angled triangle are related by the Pythagorean theorem, which states that the square of the hypotenuse is equal to the sum of the squares of the legs.
Learn more about the right-angled triangle here:
brainly.com/question/18452950
#SPJ7